The Use of Ultrasonography to Identify the Intersection of the Dorsomedial Cutaneous Nerve of the Hallux and the Extensor Hallucis Longus Tendon: A Cadaveric Study - Zdilla, Matthew J. (J Foot Ankle Surg, 2018)
Terminal branches of the superficial fibular nerve are at risk of iatrogenic damage during foot surgery, including hallux valgus rigidus correction, bunionectomy, cheilectomy, and extensor hallucis longus tendon transfer. One terminal branch, the dorsomedial cutaneous nerve of the hallux, is particularly at risk of injury at its intersection with the extensor hallucis longus tendon. Iatrogenic injuries of the dorsomedial cutaneous nerve of the hallux can result in sensory loss, neuroma formation, and/or debilitating causalgia. Therefore, preoperative identification of the nerve is of great clinical importance. The present study used ultrasonography to identify the intersection between the dorsomedial cutaneous nerve of the hallux and the extensor hallucis longus tendon in cadavers. On ultrasound identification of the intersection, dissection was performed to assess the accuracy of the ultrasound screening. The method successfully pinpointed the nerve in 21 of 28 feet (75%). The sensitivity, positive likelihood ratio, and positive and negative predictive values of ultrasound identification of the junction of the dorsomedial cutaneous nerve and the extensor hallucis longus tendon were 75%, 75%, 100%, and 0%, respectively. We have described an ultrasound protocol that allows for the preoperative identification of the dorsomedial cutaneous nerve of the hallux as it crosses the extensor hallucis longus tendon. The technique could potentially be used to prevent the debilitating iatrogenic injuries known to occur in association with many common foot surgeries.